EVALUATION OF KNOWLEDGE ABOUT DRUG PRESCRIPTION AMONG DENTAL STUDENTS; AN OBSERVATIONAL STUDY - Sadaf Amjad; Ammarah Afreen; Eruj Shuja; Zainab Khalid; Musa Raza Kazmi; Annam Zahid (Pakistan Oral & Dental Journal, 2023)
Introduction: There is a lack of research regarding dentists’ knowledge and their drug prescription practices, despite analgesics and antibiotics being frequently prescribed by dental practitioners. Prescription errors can be attributed to deficient training of dental students. This research was carried out to examine dental students’ familiarity with common drugs and whether these future graduates would be proficient in drug prescription. Study design and setting: Cross-sectional study carried out at Watim Dental College, Rawat in April, 2023. Methodology: A questionnaire consisting of 10 close-ended questions was used in this study which was conducted among 180 students of Watim Dental College. The data was analyzed using spss 26 to produce descriptive statistics, contingency tables and to run chi-square test. Results: The chief reason for prescribing medication was pain with Paracetamol being the most frequently recommended analgesic and Amoxicillin, the most commonly prescribed antibiotic. Not asking patients about drug allergies was the most common prescription error. The majority of the students used Pharmacology text books as a guide and were familiar with the WHO Guide to Good Prescribing. As the students entered their clinical years (third and final year), their drug knowledge improved which was statistically significant (p value=0.002) Conclusion: The knowledge of pharmacology among students at Watim Dental College has gaps that could be a concern to the wellbeing of the patients. Whether this affects the success and safety of treatments needs to be evaluated by further studies. It is essential to develop strict therapeutic guidelines and to deliver pharmacological therapy courses to ensure accurate drug prescription practices.